MOBILITY AND BELONGING OF STATELESS KOREANS IN JAPAN - Park , Shincha (Journal of Oriental Studies, 2024)
This study explores the subject of Chōsen identification holders among Korean residents in Japan and illustrates their complex status. In Japan’s alien registration system, Korean nationality is registered as either Chōsen or Kankoku. While the latter is linked with the Republic of Korea, Chōsen was a category originally given to those from colonial Korea who remained in Japan after the war, and is not linked a country. Nevertheless, in practice, the Japanese government tends to treat Chōsen identification holders as if they were citizens/supporters of North Korea and presumes an allegiance to North Korea. Similarly, the South Korean government often regards them with suspicion, imposing travel restrictions to South Korea and subjecting them to scrutiny at consulates. Within this environment, even among Korean residents in Japan, a pervasive misconception emerged equating Chōsen identification with North Korean nationality. This misconception significantly constrains Chōsen freedom of movement across international borders, as the international community has largely failed to comprehend the intricacies of their situation, often erroneously categorizing them as North Koreans even if individuals do not align with North Korean interests and maintain Chōsen identification based on personal convictions. This discordance between self-perception and external categorization is emblematic of the interactions between individual identities and prevailing political narratives. Within this paradoxical duality of de facto North Korean nationality and de facto statelessness, their sense of belonging is involuntarily shaped by the prevailing international political landscape, often reducing them to simply North Korean nationality, and subject to the difficulties that entails. Key words: Korean residents in Japan, nationality, alien registration, statelessness, passport